The Effect of Fluxes on the Melt Quality of AlSi7MgCu Alloy - Gyarmati, Gábor; Fegyverneki, György; Mende, Tamás; Tokár, Mónika (International Journal of Engineering and Management Sciences, 2019)
The presence of inclusions such as oxides, carbides or refractory particles can be harmful to the mechanical and surface characteristics of castings. Inclusion-rich metals result in lower fluidity and feeding capability during casting. Nowadays, solid fluxes are widely used in foundries in order to reduce the inclusion content of aluminium melts. In this study, the effect of four different fluxes on the melt quality was studied. First, the inclusion content of the flux-treated melt, and then the properties of the fluxes (i.e. chemical composition and melting temperature) were examined.